Potret Historis Hadis Pasca Khulafaur Rasyidin Sampai Pembukuan - Wely Dozan; Muhammad Yuslih (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Hadith is the source of Islamic teachings after the Qur'an which of course historically has authenticity in its development. The history of the development of hadith during the time of the Prophet was not yet organized, this means that the role of hadith during the time of the Prophet had not developed rapidly. However, as time went on with the spread of hadiths, especially after khulafaur rashidin experienced various problems such as giving false traditions, understanding various understandings of hadith.This study aims to explore the dynamics and history to reveal the chronology of the Prophet's hadith in the portrait of the hadith after khulafaur rashidin to the bookkeeping phase to go through the research studies. The fundamental aspect in this research is to explore the dynamics as well as the problems of the problems of false hadiths and the history of the development of hadith to bookkeeping.